Symbolic and numerical regression: experiments and applications - Davidson, J.W.; Savic, D.A.; Walters, G.A. (Information sciences, 2003)
This paper describes a new method for creating polynomial regression models. The new method is compared with stepwise regression and symbolic regression using three example problems. The first example is a polynomial equation. The two examples that follow are real-world problems, approximating the Colebrook–White equation and rainfall-runoff modelling. The three example problems illustrate the advantages of the new method.